Metabolic endotoxemia promotes neuroinflammation after focal cerebral ischemia. Issue 12 (December 2020) - Kurita, Naohide; Yamashiro, Kazuo; Kuroki, Takuma; Tanaka, Ryota; Urabe, Takao; Ueno, Yuji; Miyamoto, Nobukazu; Takanashi, Masashi; Shimura, Hideki; Inaba, Toshiki; Yamashiro, Yuichiro; Nomoto, Koji; et al.
Lipopolysaccharide (LPS) is a major component of the outer membrane of Gram-negative bacteria and a potent inflammatory stimulus for the innate immune response via toll-like receptor (TLR) 4 activation. Type 2 diabetes is associated with changes in gut microbiota and impaired intestinal barrier functions, leading to translocation of microbiota-derived LPS into the circulatory system, a condition referred to as metabolic endotoxemia. We investigated the effects of metabolic endotoxemia after experimental stroke with transient middle cerebral artery occlusion (MCAO) in a murine model of type 2 diabetes ( db/db ) and phenotypically normal littermates ( db/+ ). Compared to db/+ mice, db/db mice exhibited an altered gut microbial composition, increased intestinal permeability, and higher plasma LPS levels. In addition, db/db mice presented increased infarct volumes and higher expression levels of LPS, TLR4, and inflammatory cytokines in the ischemic brain, as well as more severe neurological impairments and reduced survival rates after MCAO. Oral administration of a non-absorbable antibiotic modulated the gut microbiota and improved metabolic endotoxemia and stroke outcomes in db/db mice; these effects were associated with reduction of LPS levels and neuroinflammation in the ischemic brain. These data suggest that targeting metabolic endotoxemia may be a novel potential therapeutic strategy to improve stroke outcomes.